Effect of Sitz Bath on Perineal Rupture Pain in Postpartum Mothers - Apryanti, Yohana Putri (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2024)
Perineal wounds are usually felt very painful by postpartum mothers, but there are also postpartum mothers who do not feel pain even though there is a laceration in the perineum, this happens because the pain threshold for each person is different. Perineal rupture is perineal tear when the fetus is born. This tear is traumatic because the perineum is not strong enough to withstand the stretch when the fetus passes. Efforts to reduce pain and uncomfortable conditions in mothers after postpartum and experience pain due to perineal injuries, one of which is a non-pharmacological method, namely sitz bath therapy. The aim of this study was to determine whether there was an effect of sitz bath therapy on reducing perineal wound pain in postpartum mothers. This research method is pre-experimental with the one group pretest-posttest method. The sampling technique was a purposive sample of 26 people with defined inclusion criteria, the interventions given were in accordance with the SOP and the pain scale was measured by the NRS (Numeric Rating Scale). Data analysis consisted of bivariates withpaired sampe t-test. And the results of the study obtained a value of p = 0.000 so that Ho was rejected, it was concluded that there was an effect of giving therapy with techniquessit bathon perineal wound pain in postpartum women (p <0.000). So it is recommended that sitz bath therapy is one of the therapies that reduces discomfort during recovery during the puerperium